1ISG-003 Impact of telepharmacy and community pharmacy remote-dispensing on patients on oral antineoplastic agents. (23rd March 2022) - Rodriguez, A; Fernández, X; Arderiu, A; Fando, O; Pineda, S; Urbina, J; Berzosa, M; Conde, D
Abstract : Background and importance: Oral antineoplastic agents (OAA) are dispensed through the hospital pharmacy service. COVID-19 restrictions have accelerated implementation of alternative ways of remote dispensation and pharmaceutical care to minimise patients' virus exposure. Aim and objectives: To describe the results from the implementation of an OAA remote-dispensing programme and telepharmacy to cancer patients. Material and methods: Observational prospective study from October 2020 to April 2021 in a 400-bed university hospital. Patients received virtual pharmaceutical care and agreed to collect medication at their nearest community pharmacy within our pharmacy network. A follow-up visit was made by telephone scoring level of satisfaction (1 to 10). Treatment Satisfaction Questionnaire for Medication II (TSQM v.II) was also employed to evaluate effectivity, tolerance, convenience and global satisfaction. Adherence was graded from 1 to 3 depending on the number of missed doses, where 1 meant none and 3 indicated more than four missed administrations. Demographic and treatment data were also collected. Quantitative variables were expressed as median (range) and bivariate correlations by Spearman test. Results: A total of 83 patients were enrolled; 44 (53%) patients also benefitted from telepharmacy. Demographic data: women 15 (34.1%), age 63 (42–86) years. Performance status 0: 37 (84.1%). Treatment: palbociclib 9 (20.5%), enzalutamide 7 (15.9%), ribociclib 4 (9.1%), capecitabine 3 (6.8%), nilotinib 3 (6.8%), alpelisib 2 (4.5%), bosutinib 2 (4.5%), ibrutinib 2 (4.5%). Treatment duration: 401 (7–3275) days. Administration errors were detected in 3 (6.8%) cases. Twenty-three (52.3%) with new concomitant medication, 2 (4.5%) had potential interactions with OAA. We found 12 (27.3%) patients on alternative medicine and 5 (11.4%) presented interactions. Storage errors: 1 (2.3%). Adherence: grade 1, 35 (79.5%). Twenty-nine (65.9%) adverse effects: gastrointestinal 12 (26.7%), fatigue 12 (26.7%), central nervous system 7 (15.6%), dermatological 5 (11.1%). We resolved doubts in 15 (34.1%) cases, and 3 (6.8%) patients were scheduled for follow-up appointments. Level of satisfaction with treatment delivery was 10 (8–10). TSQM v.II questionnaire: effectivity 75 (41–100), tolerance 100 (41–100), convenience 100 (50–100), global satisfaction 83 (25–100). Positive correlation: treatment duration with effectivity (rho 0.308, p=0.042). Negative correlations: adherence with adverse effects (rho 0.419, p=0.005); treatment duration with convenience and global satisfaction (rho 0.454 and 0.350, p=0.002 and p=0.020, respectively). Conclusion and relevance: Level of satisfaction with telepharmacy and remote delivery was very high. Patients with more adverse effects presented less treatment adherence. Patients with more treatment duration thought that their treatment was more effective, but the less the duration the more the level of satisfaction. References and/or acknowledgements: Conflict of interest: No conflict of interest